Understanding the factors influencing the adoption of e-wallets by Malaysian youth - Muhammad Naqib Mat Yunoh; Nurul Syahirah Mohamed Hashim; Zulkarami Che Musa; Mahathir Muhamad; Abd Aziz Mat Hassa; Norzalizah Bahari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
E-wallets have become increasingly popular around the world. This research was conducted to study the relationship between the factors and adoption of e-wallet. The population that involved in this research is youths at Teluk Intan, Perak. This study will investigate the relationship between independent variable with dependent variable. The independent variables for this research are social influence, perceived security and trust while the dependent variable is adoption of e-wallet. To ensure that the study purpose is archived, quantitative research was used for the analysis to analyse the result and the sampling technique. A set of 379 questionnaire will be used to collect data from the selected respondent among youths at Teluk Intan, Perak. The 379 respondents were from different age, gender and hometown. Thus, this research is to identify the factors that affecting the adoption of E-wallet among youths at Teluk Intan, Perak. The result for this research has been proven by using the reliability analysis, descriptive analysis and Pearson’s correlation. All hypothesis also approved for this research. According this research, the factors of social influence, perceived security and trust were significant and it influence the youths towards the adoption of e-wallet.